(untitled) (CIPEEX, 2025)
The objective of this study is to understand how labor compliance can act as a tool to implement the commands of the General Data Protection Law in companies, considering the processing of employee data. The result was that compliance is an effective way for companies to adapt so that they comply with the processing and storage of their workers’ data. Through a literature review, it became clear that labor compliance helps companies adapt to the legislation in question, allowing greater organization and effectiveness in the implementation of the conduct contained in the LGPD. It was possible to conclude that the General Data Protection Law needs to be established in the labor market, especially in relation to employees’ sensitive data and labor compliance acts to safely implement legal commands so that employers do not respond for the lack of security in the processing of this data.